Acceptance of seniors towards automatic in home fall detection devices. Issue 4 (19th December 2016) - Feldwieser, Florian; Marchollek, Michael; Meis, Markus; Gietzelt, Matthias; Steinhagen-Thiessen, Elisabeth
Abstract : Purpose: Senior citizen falls are one of the highest-cost factors of healthcare within this population group. Various approaches for automatic fall detection exist. However, little is known about the seniors' acceptance of these systems. The purpose of this paper is to investigate the acceptance of automatic fall detection devices as well as the technological commitment and the health status in community-dwelling adults with a predefined risk of falling. Design/methodology/approach: Seniors with a risk of falling were equipped with either an accelerometer or an accelerometer with an additional visual and optical fall detection system in a sub-group of the study population for a period of eight weeks. Pre- and post-study questionnaires were used to assess attitudes and acceptance toward technology. Findings: In total, 14 subjects with a mean age of 75.1 years completed the study. Acceptance toward all sensors was high and subjects were confident in their ability to handle technology. Medical assessments showed only very mild physical and no mental impairments. Measures that assured subjects privacy protection were welcomed. Sensor technology should be as unobtrusive as possible. Originality/value: Privacy protection and uncomplicated use of the fall detection equipment led to high acceptance in seniors with high-technical commitment and good health status. Issues to further improve acceptance could be identified. Future research on different populations is necessary.